1
$\begingroup$

Find $\;\dfrac{dy}{dx}\;$ given $\;e^{9x}= \sin(x+9y)$

the answer is $\;\displaystyle\frac{e^{9x}}{\cos(x+9y)}- \frac{1}{9}$.

Can you show the process of how this is worked?

thanks.

$\endgroup$
2
$\begingroup$

Differentiate both sides of your equation using chain rule $$ \left( e^{9x} \right )' = \left ( \sin (x+9y) \right )'\\ 9e^{9x} = \cos (x+9y) \cdot (x + 9y)' = \cos (x+9y) \cdot (1+9y') $$ From which you can find that $$ 1+9y' = \frac {9e^{9x}}{\cos (x+9y)} \\ y' = \frac {e^{9x}}{\cos (x+9y)}-\frac 19 $$

$\endgroup$
1
$\begingroup$

Let's start by taking derivatives with respect to $x$ at both sides of the equation. We get

$$\frac{d}{dx}(e^{9x}) = \frac{d}{dx}(\sin(x + 9y))$$ which gives, by applying the chain rule and remembering that $y$ is a function dependent on $x$ $$9e^{9x} = \cos(x + 9y)(1 + 9\frac{dy}{dx})$$ Now dividing both sides by $\cos(x + 9y)$ gives $$\frac{9e^{9x}}{\cos(1+9y)}= 1 + 9\frac{dy}{dx}$$ from which we can deduce $$\frac{9e^{9x}}{\cos(1+9y)} - 1 = 9\frac{dy}{dx}$$ and so $$\frac{e^{9x}}{\cos(1+9y)} - \frac{1}{9} = \frac{dy}{dx}$$

$\endgroup$
0
$\begingroup$

Taking the derivative with respect to $x$ on the left-hand side is basic stuff. For the right-hand side, use the chain rule (with the assumption that $y$ is a function of $x$) to get $$\begin{align}\frac{d}{dx}\bigl[\sin(x+9y)\bigr] &= \cos(x+9y)\cdot\frac{d}{dx}[x+9y]\\ &= \cos(x+9y)\cdot\left(1+9\frac{dy}{dx}\right).\end{align}$$ Now set your left-hand side's derivative equal to your right-hand side's derivative, and solve for $\cfrac{dy}{dx}.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.